The Effect of Plyometric Training on Improving Values of Some Biokinematics Variables of High-Jump Shooting Skill with the Accuracy in Handball (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study aimed to find out the effect of plyometric training on improving values of some kinematicsvariables of high-jump shooting skill and accuracy in Handball.The researcher used the single group experimental design. The research sample was the players of NaftAl-Janoob Club, season 2020- 2021, they were chosen intentionally. The researcher photographed theresearch sample using a camera. “Sony” (250 images/sec), And he conducted the kinematic analysisusing the “dart-fish” program. The implementation of the proposed training curriculum continued for(8) weeks at (24) training units and a rate of (3) training units per week. The researcher took intoaccount the time specified for each training unit and the number of training units per week, and thegeneral capabilities of the players, as well as the availability of devices and tools, as the researcher wasensured that the curriculum vocabulary is consistent with the scheduled exercises prepared previouslyfor the team. the researcher concluded that there was an improvement in the values of kinematicsvariables while applying the plyometric training through the results of pre and posttests and for thefavor of posttest, as well as the used training method that included plyometric training improved theshooting accuracy performance in high shooting in the post-test due to the use of the same exercisesof the motor pathway. The researcher recommended using plyometric training to develop the values ofkinematics variables of high-jump shooting skill.
Keywords: Plyometric Training , High-Jump Shooting , Accuracy in Handball